Photoresponsive luminescent polymeric hydrogels for reversible information encryption and decryption - Li, Zhiqiang (2020)
Conventional luminescent information is usually visible under either ambient or UV light, hampering their potential application in smart confidential information protection. In order to address this challenge, herein, light-triggered luminescence ON-OFF switchable hybrid hydrogels are successfully constructed through in situ copolymerization of acrylamide, lanthanide complex, and diarylethene photochromic unit. The open-close behavior of the diarylethene ring in the polymer could be controlled by UV and visible light irradiation, where the close form of the ring features fluorescence resonance energy transfer with the lanthanide complex. The hydrogel-based blocks with tunable emission colors are then employed to construct 3D information codes, which can be read out under a 254 nm UV lamp. The exposure to 300 nm UV light leads to the luminescence quenching of the hydrogels, thus erasing the encoded information. Under visible light (>450 nm) irradiation, the luminescence is recovered to make the confidential information readable again. Thus, by simply alternating the exposure to UV and visible lights, the luminescence signals could become invisible and visible reversibly, allowing for reversible multiple information encryption and decryption.